En Bloc Resection of Right Renal Cell Carcinoma and Inferior Vena Cava Tumor Thrombus Without Caval Reconstruction: Is It Safe to Divide the Left Renal Vein? - Horodyski, Laura; Gonzalez, Javier; Tabbara, Marina M.; Gaynor, Jeffrey J.; Rodriguez-Cabero, Maria; Herranz-Amo, Felipe; Hernández, Carlos; Shah, Rushi; Ciancio, Gaetano (Frontiers in Oncology, 2022)
Introduction: It has been suggested that inferior vena cava (IVC) reconstruction following resection of retroperitoneal tumors with IVC tumor thrombus (TT) is not required when adequate collateral circulation is present. There are no reports evaluating mid- and long-term effects on renal function in these patients. The purpose of this study was to assess renal function after en bloc resection of right renal cell carcinoma (RCC) with obstructing IVC TT and the possible risks that may arise after left renal vein division. Materials and Methods: A bi-institutional retrospective review was performed over a 15-year period, assessing patients with right RCC and obstructing level II-IV tumor thrombus. All patients underwent extensive evaluation and cardiology clearance, and informed consent was obtained for right radical nephrectomy and thrombectomy with or without IVC reconstruction with possible cardiopulmonary bypass (CPB). Patient demographics, tumor characteristics, intra-operative factors, complications, length of stay, and patient survival were evaluated. Pre-operative creatinine was recorded, as was creatinine on day of discharge, and at 6- and 12-months post-operatively. Results: Twenty-two patients were included in the study. Median age-at-surgery was 62.5 (range 45-79) years, and 19 (86%) of the patients were male. One patient (5%) had a level II thrombus, 14 patients (64%) had a level III thrombus (IIIa n=3, IIIb n=6, IIIc n= 3, IIId n=2), and seven patients (32%) had a level IV thrombus. Intra-operatively, median estimated blood loss was 1.35 (range: 0.2 – 25) L. The median length of hospital stay was 11 (range: 5 – 50) days. Median preoperative creatinine was 1.20 (range: 0.40 – 2.70) mg/dL, and postoperatively, median creatinine was 1.3 (range: 0.86 – 2.20) mg/dL. Median creatinine at 6 months and 12 months post-operatively were 1.10 (range 0.5 – 1.8) and mg/dL 1.40 (range 0.6 – 2.0), respectively. Four patients died (range: 0.1-1.3 years), and median post-operative follow-up among 18 ongoing survivors (at last follow-up) was 1.5 (range: 0.5-7.0) years. Conclusions: Resection of right RCC with an obstructing level II-IV TT without reconstruction of the IVC appears to not have a significant adverse effect on mid-term renal function after division of the left renal vein.